Aviation portal as a hub of information on the activities of air transport in Ukraine - Жуков, І. А.; Городиський, В. Б.; Мельникова, Т. П. (Problems of Informatization and Control, 2004)
The problem of creation of the specialized Ukrainian portal is considered. General-system requirements structure of an aviation portal, and also the requirement to his software are designated. The created portal of aviation subjects can be taken for a basis at construction of a full- scale portal of an air transportation of Ukraine